2008
DOI: 10.1007/s11085-008-9096-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SO2 on the Oxidation of 304L Steel in O2 + 40%H2O at 600 °C

Abstract: The effect of sulphur dioxide on the oxidation of alloy 304L in O 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…In contrast, recent studies [22][23][24] have revealed beneficial effects of SO 2 with regard to oxidation rates of iron in certain conditions. The reason for decreased oxidation rates by SO 2 was attributed to the presence of sulphate on the oxide surface of iron [22][23][24]. This effect was postulated to be due to a decreased activity of oxide ions on the hematite surface caused by adsorbed sulphate blocking the surface sites where oxide ions are generated.…”
Section: Effect Of So 2 On Scale Morphologymentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, recent studies [22][23][24] have revealed beneficial effects of SO 2 with regard to oxidation rates of iron in certain conditions. The reason for decreased oxidation rates by SO 2 was attributed to the presence of sulphate on the oxide surface of iron [22][23][24]. This effect was postulated to be due to a decreased activity of oxide ions on the hematite surface caused by adsorbed sulphate blocking the surface sites where oxide ions are generated.…”
Section: Effect Of So 2 On Scale Morphologymentioning
confidence: 84%
“…In contrary to that, beneficial effects of SO 2 against oxidation of pure Fe and Fe-base alloys, if present in trace amounts (1-1000 ppm) in the temperature range of 450-650°C, has been recently reported [22][23][24]. The inhibitive effect of SO 2 was attributed to a small amount of sulphate found at the gas/oxide interface of the alloys.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies [11,[22][23][24][25][26][27] suggest that SO2 in the flue gas can affect the corrosion process in a couple of ways:…”
mentioning
confidence: 99%
“…In this process, SO2 is also converted to SO3, (b) formation of surface sulphates which prevent the vaporisation of CrO3(OH)2 and thus, slow down the corrosion process [26,27], and; (c) the ability of surface sulphates to inhibit surface reactions involved in corrosion [27].…”
mentioning
confidence: 99%